PENGARUH MODEL PEMBELAJARAN TEAM ASSITED INDIVIDUALIZATION TERHADAP HASIL BELAJAR IPAS KELAS V DI MIN 4 BANDAR LAMPUNG - Rifka Maulia Putri; Chairul Amriyah; Yuli Yanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of the Team Assisted Individualization (TAI) model on the science learning outcomes of fifth-grade students at MIN 4 Bandar Lampung with a focus on analytical skills (C4). The study used a quasi-experimental design with two classes (VA and VB, each with 20 students) selected through purposive sampling. The instrument was a multiple-choice test with 30 items, and 20 of them were declared valid and reliable (α = 0.847). The data were normally distributed and homogeneous, so they were analyzed using an independent samples t-test. The results showed a significant difference between the experimental class (mean = 86.75) and the control class (mean = 79.75) with t(38) = −2.121 and p = 0.040. The increase in the achievement of the C4 indicator indicates the effectiveness of TAI in developing students' analytical skills. These findings recommend the implementation of TAI in Madrasah Ibtidaiyah as a collaborative learning strategy that supports the implementation of the Independent Curriculum.